ANALISIS KEBUTUHAN TENAGA KEPERAWATAN BERBASIS BEBAN KERJA DENGAN METODE WORKLOAD INDICATOR STAFF NEED (WISN) DI INSTALASI GAWAT DARURAT (IGD) RUMAH SAKIT IBU DAN ANAK PROVINSI ACEH - Fajri, Nadia; Yusni, Yusni; Usman, Said; Syahputra, Irwan; Nurjannah, Nurjannah (Jurnal Kesehatan, 2020)
Abstract Background: The problem of shortage of medical personnel must be considered properly, whether it really requires additional manpower due to excessive workloads which will affect the quality provided or the amount of unproductive time spent by HR while on duty. This also happened at the Aceh Province Mother and Child Hospital, there are plans to increase the number of staff carried out at the Mother and Child Hospital who need to use workload calculations, the reality on the ground is that the planning of medical personnel in RSIA is only based on the request of the work unit and the comparison of calculations between the number of medical personnel with BOR, LOS and others or because of the increase in the class of the hospital and the lack of qualifications of each type of medical staff. Objective: to analyze the need for workload-based nursing personnel using the Workload Indicator Staff Need (WISN) method in the Emergency Departments (ED) Mother and Child Hospital, Aceh Province. Research Methods: This research is a descriptive study, using a work sampling method, namely all the activities of nurses who served in the IGD RSIA Aceh Province as respondents who were examined every time for four days. The population in this study were all nurses in the Emergency Departments (ED) of the Aceh Province Hospital in 2020 totaling 19 people, the samples in this study were all nurses in the Emergency Departments (ED) with a total sampling of 19 people. The calculation of the need for nurses using the WISN method. Results: the workload of health workers in RSIA Aceh Province can be seen from the details / job descriptions of the job, the amount of time required for each task, the time for completing tasks is a multiplication of the workload with the norm of time and the number of hours of effective working time. Besides being influenced by the number of workers, the workload of health workers can also be influenced by the number of patients and the conditions of the workplace environment. Conclusion: the results of the WISN calculation show that the health personnel at RSIA Provini Aceh still lacks 1 nurse in the ED. The shortage of health workers will have an impact on the high workload of health workers in each sector.